VD_FINDINFO HC / 2013 / 445 vom 21. Mai 2013 - VD Tribunal cantonal (2013)
AVANCE DE FRAIS, QUALITÉ DE PARTIE, PRINCIPE DE L'ÉQUIVALENCECONTRIBUTION CAUSALE, RÉDUCTIONEN GÉNÉRAL | 103 CPC (CH), 98 CPC (CH), 10 TFJC (2010), 22 al. 8 TFJC (2010), 9 al. 1 TFJC (2010)